Cardiovascular benefits of Tirzepatide: A breakthrough in cardio-metabolic care - Majid, Maham; Haider, Ehtisham; Fatima, Ghania (Journal of the Pakistan Medical Association, 2025)
Diabetes mellitus (DM), a long-term condition when the body can’t produce or utilise insulin, leading to increased blood glucose levels, globally affects 10.5% of adults today and is projected to grow to 12.2% by 2045. Among them, over 90% of cases heighten the risk of heart issues such as heart failure (HF), stroke, and coronary artery disease, resulting in approximately 6.7 million deaths in 2021, so early detection and effective management are paramount. [1] Certain antidiabetic medications come with increasing heart-related issues; for example, sulfonylureas and thiazolidinediones can cause arrhythmias, myocardial infarction, and fluid retention with heart failure. Others, like GLP-1 agonists, Glinides, and DPP-4 inhibitors, demonstrate varying impacts on heart conditions. [2] However, tirzepatide, an FDA-approved drug, has shown promise in reducing cardiovascular incidents among these individuals. [3] Recent large clinical trials have highlighted the heart health benefits of tirzepatide for Type 2DM patients. The SURPASS-4 trial illustrated its ability to lower major adverse cardiovascular events (MACE), lower cardiovascular mortality, and improve cholesterol levels when compared to other medications like dulaglutide (found in the SURPASS CVOT trial). The SUMMIT evaluates its effectiveness and safety in heart failure patients with preserved ejection fraction. Moreover, post hoc studies (SURMMOUNT-1) reveal a significant reduction in the estimated risk for cardiovascular disease (CVD) over a decade. [4] In another study, tirzepatide also reduced systolic blood pressure and inflammatory and endothelial dysfunction biomarkers. [5] However, the shorter duration of some trials compared to FDA-recommended timelines for cardiovascular outcomes studies remains a limitation. Not only does tripeptide help manage blood sugar and weight, but it also benefits heart health by improving lipid profile and reducing inflammation while enhancing blood circulation. [4] This could potentially thwart conditions like atherosclerosis, making it a potential therapeutic option for managing CVD and HF in T2DM patients, particularly with family history or other risk factors. Although the findings are optimistic, additional randomized controlled trials (RCTs) are necessary in Asian populations to comprehensively grasp its impact. Despite mild gastrointestinal side effects that are frequent overall, Tirzepatide demonstrates promising results. Further investigation is needed to understand the impact of GIP in Tirzepatide's effects on the heart and its link to GLP-1. Additional research could investigate its significance for conditions like alcoholic fatty liver disease (NAFLD), kidney protection, and neuroprotection. These observations highlight the importance of conducting trials over an extended period to investigate its healing capabilities thoroughly.